Evaluasi Program Pembinaan Kerohanian Peserta Didik Pada Kurikulum Merdeka di SMP Negeri 2 Manuhing (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to evaluate the spiritual guidance program for students in the context of implementing the Merdeka Curriculum at SMP Negeri 2 Manuhing. The focus of the study includes the role of Islamic, Christian, and Hindu Kaharingan teachers, the forms of guidance activities, the obstacles encountered, and strategies for strengthening and developing evaluation instruments based on local wisdom. This study uses a qualitative approach with observation, in-depth interviews, and documentation of the principal, religious teachers, and students. The results show that the implementation of spiritual guidance reflects the spirit of the Merdeka Curriculum by emphasizing flexibility, contextual values, and character-based learning. However, its implementation is still sectoral in nature per religion, not yet integrated across faiths, and constrained by limited facilities, teacher competence, and the absence of formal policies. Strengthening efforts are directed at three main dimensions, namely institutional, pedagogical, and cultural, through the formation of an interfaith team, reflective training, and the integration of local Dayak Kaharingan cultural values into learning. In addition, this study developed a Kaharingan-based spiritual guidance evaluation instrument with four main dimensions: spirituality, moral-ethics, socio-culture, and personal reflection. This instrument is designed to assess students' spiritual development holistically and contextually, in accordance with the multicultural character of the school